Alteration of CD4CD25Foxp3 T cell level in Kawasaki disease - Su Ye Sohn; Young Wooh Song; Yun Ku Yeo; Yun Kyung Kim; Gi Young Jang; Chan Wook Woo; Jung Hwa Lee; Kwang Chul Lee (Korean Pediatric Society, 2011)
PurposeExaggerated pro-inflammatory reactions during the acute phase of Kawasaki disease (KD) suggest the role of immune dysregulation in the pathogenesis of KD. We investigated the profiles of T regulatory cells and their correlation with the clinical course of KD.MethodsPeripheral blood mononuclear cells were collected from 17 KD patients during acute febrile and subacute afebrile phases. T cells expressing CD4, CD25, and Foxp3 were analyzed using flow cytometry, and the results were correlated with the clinical course of KD.ResultsThe percentage of circulating CD4+CD25highFoxp3+ T cells among CD4+ T cells was significantly higher during the subacute afebrile phase than during the acute febrile phase (1.10%±1.22% vs. 0.55%±0.53%, P=0.049). Although levels of CD4+CD25lowFoxp3+ T cells and CD4+CD25-Foxp3+ T cells were only slightly altered, the percentage of CD4+CD25+Foxp3- T cells among CD4+ T cells was significantly lower during the subacute afebrile phase than during the acute febrile phase (2.96%±1.95% vs. 5.64%±5.69%, P=0.036). Consequently, the ratio of CD25highFoxp3+ T cells to CD25+Foxp3- T cells was higher during the subacute afebrile phase than during the acute febrile phase (0.45%±0.57% vs. 0.13%±0.13%, P=0.038).ConclusionDecreased CD4+CD25highFoxp3+ T cells and/or an imbalanced ratio of CD4+CD25highFoxp3+ T cells to CD4+CD25+Foxp3- T cells might play a role in KD development. Considering that all KD patients were treated with intravenous immunoglobulin (IVIG), recovery of CD4+CD25highFoxp3+ T cells during the subacute afebrile phase could be a mechanism of IVIG.